Possibilidades para a prevenção de violência de gênero nas escolas a partir de um relato de experiência - Arrebola, Fernanda Salustiano (Universidade Federal de São Carlos, 2026)
This paper presents an experiential account that analyses school experiences marked by various manifestations of gender-based violence, drawing on the relationship between the author’s formative memories—particularly during her supervised teaching placement—and theoretical frameworks of Dialogic Feminism (DF) and Dialogic Learning (DL), within the context of Learning Communities (LC). The situations described highlight the persistence of historically structured inequalities that manifest themselves through physical, symbolic, psychological and institutional violence, affecting girls and women. The methodology is grounded in the qualitative analysis of lived experiences, interpreted in the light of national and international studies discussing gender, education, violence and transformative pedagogical practices. The results indicate that the absence of intentional educational interventions favours the normalisation of stigmas, whilst practices based on egalitarian dialogue, the participation of the entire school community and the valuing of differences contribute to the construction of inclusive and safe school environments. Thus, it is concluded that the school, by adopting a critical stance committed to social justice, can become a space for the prevention of violence and the promotion of democratic relationships from early childhood onwards, fostering transformation in the lives of all members of the community.
Ways to prevent gender-based violence in schools, based on an account of personal experience
Keywords: Violência de gênero; Feminismo dialógico; Aprendizagem dialógica; Gender-based violence; Dialogical feminism; Dialogical learning; CIENCIAS HUMANAS::EDUCACAO; 5. Igualdade de Gênero; 4. Educação de Qualidade